2002
DOI: 10.1088/0953-4075/35/4/319
|View full text |Cite
|
Sign up to set email alerts
|

The second Born approximation in electron-atom collisions in the presence of a laser field

Abstract: The second-order Born approximation (SBA) has been used to calculate the differential cross section for electron-hydrogen collisions in the presence of a linearly polarized laser field. We present a more precise treatment of the small-energy region of an incident electron by improving the calculation of the second Born term in this energy region. Detailed calculations of the scattering amplitudes are performed by using the Sturmian basis expansion. Our SBA results agree very well with those obtained in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…[15]). More recently an experiment was performed at higher laser frequencies [16] and theory was developed beyond a perturbative treatment [17][18][19].…”
mentioning
confidence: 99%
“…[15]). More recently an experiment was performed at higher laser frequencies [16] and theory was developed beyond a perturbative treatment [17][18][19].…”
mentioning
confidence: 99%
“…We present here a short description of our theoretical approach to deal with the electron's impact excitation of the helium atom in the presence of a laser field. A detailed description can be found in our previous works [32][33][34]. The scenario we considered here can be simplified into the following form:…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…The wave functions ψ i , ψ f , and ψ n are the stationary states associated with the eigenenergies E i , E f , and E n of the helium target, respectively. These states were evaluated using the Sturmian approach (see [26,34,36]).…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…In the region of high intensity, theoretical calculations using Floquet R-Matrix theory cannot reproduce experimental results [50] and for some electron energies in question the contribution from the second-Born approximation will also be negligible [51]. Since both laser-target effects [50], as well as second-Born contributions [51] do not readily explain experimental data, it seems reasonable, also in view of the more recent experimental results, to re-evaluate some of the other aspects of the scattering process, drawing on recent knowledge from other parts of strong-field physics. To this end, we note that multiple studies on strong-field ionisation (see, e.g., references [52][53][54][55][56][57][58]) have reported that a breakdown of the D approximation for infrared fields appeared at intensities comparable to the highest intensity used in LAES-experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-assisted scattering therefore remains a research area with open questions, and with the introduction of femtosecond lasers, new applications as well as new challenges occur [8,9]. In the region of high intensity, theoretical calculations using Floquet R-Matrix theory cannot reproduce experimental results [50] and for some electron energies in question the contribution from the second-Born approximation will also be negligible [51]. Since both laser-target effects [50], as well as second-Born contributions [51] do not readily explain experimental data, it seems reasonable, also in view of the more recent experimental results, to re-evaluate some of the other aspects of the scattering process, drawing on recent knowledge from other parts of strong-field physics.…”
Section: Introductionmentioning
confidence: 99%